Strategy Development of Perumda Air Minum Performance Improvement using Combination of Balance Scorecard, SWOT and QSPM Methods - Zilvia Wulandari; Shinta Indah; Denny Helard (Universitas Negeri Padang, 2025)
The provision of drinking water is one of the basic needs and socio-economic rights of the community that must be fulfilled by the Government, both the Regional Government and the Central Government. Increasing access to drinking water is closely related to improving the performance of Perumda as a business unit providing drinking water. Perumda Air Minum Tirta Alami Tanah Datar Regency is the only BUMD that provides drinking water in Tanah Datar Regency. As a company that organizes the Drinking Water Supply System (SPAM), Perumda Air Minum is required to be able to provide the best possible service in providing clean water to the community. The performance evaluation study of Perumda Air Minum Tirta Alami Tanah Datar Regency was carried out in general through some stages; data inventory, performance evaluation and determination of performance status. The performance assessment uses four aspects, namely service, operational, human resources and financial aspects for the period of 2023. From the results of the evaluation of the four aspects, the performance of Perumda Air Minum Tirta Alami Tanah Datar Regency showed a quite good performance, with a total indicator value of all aspects of 3.10. This shows that the company can be categorized as healthy because it has a total value of more than 2.8. Based on this study, it is expected that the company can strive to improve performance on indicators that still obtain values that do not meet the predetermined standards.